EFFECT OF PLANT DENSITIES ON GROWTH CHARACTERS, SILAGE AND GRAIN YIELD OE CORN (Zea mays L.) - Salim Younis; Abbas. M. Al-Hasans. (Mesopotamia Journal of Agriculture)
A Field experiment was Carried out in autumn Season of 2012 at AL- Hemidat / thaljah village 20km to the West of Mosul city and Bhashiqa / Tobzawh village 25 km east of Mosul City to Study the effect of three Plant densities(200, 300 and400 thousand plant/ha) on growth characters, silage and grain yield of two corn varieties The experiment was applied by using Randomized Compelt Blok Desing (R.C.B.D) with three replications. The results showed that there were no significant differences between the variety Bohoth 106 and Sara for all growth characteristics, silage and Grain yield at both locations except that for leaf area index and leaves percentage at Tobzawh and Number of Leaves at both locations The plant density 400 Thousand Plant/ha gave a highest silage yield for both locations, while The plant density 200 Thousand Plant/ha gave a highest grain yield at both locations The interaction between plant density and varieties was significantly affected on silage growth characters, grain yield at both locations except for Leaves percentage at / thaljah locations, plant height and number of leaves at both locations The highest silage yield was obtained from Bohoth106at 400000 plant/ha in Tobzawh (52.0tons/ha) and Thaljah (50.0tons/ha) The highest grain yield was acheaved with Sara at 200000 plant/ha in Tobzawh (3.25.tons/ha) and Thaljah (3.28tons/ha).